Analisis faktor Penyebab Kejadian Asfiksia Pada Bayi Baru Lahir di RS Aura Syifa Kabupaten Kediri - Nurita Nilasari Bunga Kharisma Arifiana Putri (Journal of Ners and Midwifery, 2019)
Neonatal asphyxia is a state in which the baby can not breathe spontaneously and regularly after birth. This is caused by hypoxia fetus in the uterus, and result in high morbidity and mortality in newborns. The incidence of neonatal asphyxia in Indonesia is still around 37% in 2013. The trend improvement happen asphyxia in newborns of 0.5 to 1.3% in 2012 to 2014 in the Aura Syifa Hospital Kediri.Â The purpose of this study to prove the causes of maternal, umbilical cord factors, infant factors, and other factors related to asphyxia. The study design was cross-sectional. Sample study of 200 newborns asphyxia, taken by systematic random sampling, data was collected from medical record documentation study. Data were analyzed using univariate, bivariate with chi square test and multivariate logistic regression test.Â Variables influencing the asphyxia in this study are variable placental abruption, winding umbilikal cord, knot umbilikal cord, parity, and low birth weight, abnormalities location variable layout is a dominant factor against asphyxia with OR 1.772. This means that mothers with the disorder lies the risk 1.7 times more likely to give birth asphyxia compared with women who did not experience abnormal location after controlling for variables low birth weight, placental abruption, and knot umbilikal cord.